Application of Organosilicon Modifier Based on Tetraethoxysilane for the Production of Heat-Resistant Chrysotile Fibers and Reinforced Cement Composites - Roman Nikolaevich Yastrebinsky; Vyacheslav Ivanovich Pavlenko; Anna Viktorovna Yastrebinskaya; Andrey Ivanovich Gorodov; Anastasia Vladislavovna Akimenko (Fibers, 2023)
This research is aimed at obtaining boron-containing nanotubular chrysotile fibers with increased neutron absorption capacity. The possibility of using an organosilicon modifier based on tetraethoxysilane to increase the hydrothermal stability of chrysotile, as well as the strength of nanoreinforced composites based on a cement binder is considered. The mechanisms for the synthesis of heat-resistant nanotubular fibers of the composition Mg6(OH)8SiB4O10, which have a chrysotile structure, have been established. To increase the hydrothermal stability of chrysotile, crystalline hydrate phases were localized inside nanotubes using amorphous silica formed as a result of hydrolysis of silicon alkoxide under hydrothermal conditions in an alkaline environment. The modification of chrysotile via amorphous silica increases its hydrothermal stability by 97 °C. It is shown that the introduction of an organosilicon modifier based on tetraethoxysilane into the composition of Portland cement composite material leads to an increase in the structural strength and density of the composite due to the activation of silicate formation processes in the cement matrix, especially under hydrothermal conditions. The experiments showed that the strength of silicon alkoxide-modified samples of composite material increased by 34%.